THE SECURITY CULTURE AS A FOUNDATION OF THE SOCIETY’S WELFARE - SPRINCEAN SERGHEI (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2019)
The socio-political, economic, cultural, religious, ethical, mental or technological-communicative differences, with a major impact on the living standards, on the quality of life standards in human communities inhabiting the planet Earth, contribute to the strengthening of mankind’s potential to cope with the most violent and destructive effects and results of the multidimensional global crisis, through the diversity of chances and identities it generates. The central concern in the process of building security culture as a state policy is the strengthening of human security with its new aspects in the context of the security approach to the building of a knowledge-based society, of a morally refurbished society, rebuilt on noospheric and bioethical principles.